The Effectiveness of Project-Based Learning Integrated with Canva and Mathematical Aptitude on Whole Number Learning in Elementary School Students - Rachmawati, Rina; Sitompul, Nurmida Catherine; Rusmawati, Retno Danu (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Mathematics learning in elementary schools still faces challenges, particularly in the topic of arithmetic operations with whole numbers, which requires conceptual understanding and precision. Furthermore, learning remains teacher-centered and has not yet optimally utilized digital media. Canva, as a digital medium, actually has the potential to provide engaging and interactive visual displays. This research gap arises because there are still few studies that simultaneously compare the effectiveness of Project-Based Learning (PjBL) and Canva-assisted Expository Learning and examine the role of mathematical aptitude as a moderating variable. This study aims to analyze the influence of learning strategies, mathematical aptitude, and their interaction on learning outcomes in arithmetic operations with whole numbers up to 100,000. The approach used was quantitative with a 2x2 factorial experimental design involving 86 fifth-grade students. The research instruments consisted of a learning achievement test and a mathematical aptitude questionnaire. The results of a two-way ANOVA analysis showed that Canva-assisted PjBL was more effective than Expository Learning, mathematical aptitude had a significant effect, and there was an interaction between the two, with PjBL being more helpful for students with lower aptitude. This study confirms that Canva integration in PjBL is effective for 21st century learning.